VULNERABILITY ASSESSMENT DAN PENETRATION TEST PADA WEBSITE MA/MTS HUSNUL KHATIMAH KUNINGAN - Mohamad Fathurahman; Zulhelman; Abdul Aziz (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
The internet facility employed almost every field of work and people have become dependent on it. Concerns about information security have increased including the world of education especially during this pandemic, is done via the internet. That’s why the element of security is so important for any website. Attention to web security is very high carried out by government agencies, educational institutions, and the financial sector. If the stored data can be hacked then hackers can use the data illegally and can lead to crime. It is important to test the security of web applications by conducting penetration tests to identify web application vulnerabilities and actions taken by hackers. This research will focus on web application security. The output of the vulnerability test is in the form of a report that contains a description of the vulnerabilities that exist on the website. Through the analysis of the output of the vulnerability assessment, it is possible to improve the security of the site and then test it again with a penetration test. Through the identification of web security vulnerabilities, improvements had been made to increase the security level of the application website until it reaches a low level.